Strategi Komunikasi Majelis Taklim Dalam Peningkatan Perilaku Akhlak Remaja : (Studi kasus Majelis Taklim di Mesjid Darul Huda Buloh Blang Ara) - Jafar, Muhammad (Yayasan Madinah Al-Aziziyah, 2023)
This research aims to identify communication patterns of study circles (majelis taklim) for the purpose of enhancing behavior and nurturing the ethics of contemporary adolescents. The research seeks to determine the communication barriers faced by study circles in their efforts to improve behavior and cultivate the morals of today's youth. The research methodology employed in this study is qualitative research, utilizing observation, interviews, and documentation techniques. The study draws on both classical and modern organizational communication theories. The findings of this research reveal that the communication patterns of the study circle at Darul Huda Mosque in Buloh Blang Ara, as a means of enhancing behavior and nurturing the ethics of contemporary youth, include inviting young members of the community to attend religious lectures, creating a comfortable learning environment for study circles, coordinating with the local village administration, and orally emphasizing the importance of seeking knowledge to the youth. The communication barriers faced by the study circle in Darul Huda Mosque, Buloh Blang Ara, in their efforts to improve behavior and cultivate the morals of today's youth, include clashes in scheduling with other activities, lack of discipline among youth participants in attending study circles, and a general lack of willingness among the youth to engage in religious learning.